promotion image of download ymail app

1 Answer

  • 9 years ago
    Favorite Answer

    (a) C: (x,y,z)=(4, t, t^2), t=-1~3

    ds=√(0+1+4t^2) dt

    ∫_C xy ds= ∫_[-1,3] 4t√(1+4t^2) dt

    = (1/3)(1+4t^2)^(3/2) sub. t=-1~3

    = (37√37 - 5√5)/3


    (i) curl(F)= ( x-x, y-y, z-z) =(0, 0, 0), so that F is irrotational.

    div(F)=2x+0+0=2x, not zero, so that F is not solenoidal

    (ii) ∂φ/∂x= yz , then φ=xyz+x^3/ 3+ C1(y, z)

    ∂φ/∂y=xz, then φ=xyz+C2(z,x)

    ∂φ/∂z=xy, then φ=xyz+C3(x,y)

    thus φ=xyz+ x^3 / 3+ C (constant independent on x,y,z)

    • Commenter avatarLogin to reply the answers
Still have questions? Get your answers by asking now.